Desenvolvimento de uma sonda resistiva para o monitoramento da condutividade elétrica de soluções nutritivas em hidroponia - Sá, Klênio Bezerra de (2017)
Hydroponics is an agricultural technique that provides several benefits to producers, such as higher productivity, lower production cycle, off-season production and better control of production scheduling. However, in order to obtain the best productive indexes, one should make use of the available resources efficiently. In this context, automation appears as an ally in the improvement of processes in the most different aspects and particularities of this activity, such as, for example, control of light, temperature, air humidity, electrical conductivity of the nutrient solution and interval and duration of this solution. Among these aspects, the electrical conductivity plays a fundamental role in the production process, since this parameter is indicative of the concentration of salts in the solution, which influences the intensity with which the nutrients are assimilated by the plants, directly reflecting the characteristics of the product. The objective of this research was the development and evaluation of a resistive sensor for monitoring the electrical conductivity (EC) of the nutrient solution. This project was based on two electronic circuits widely used for the most different purposes, the Wheatstone bridge and the instrumental amplifier, which, in this case, are used to measure the variation of the electrical resistance of a nutrient solution. Both circuits were printed on an electronic circuit board in which stainless steel electrodes were added, which interface between the nutrient solution and the circuit. The sensor was parameterized with a hand-held conductivity meter with variable scale from 0 to 2000 μS/cm model CD-203. EC data were monitored during the assisted variation of constituent nutrient concentration. A regression analysis was performed, generating a model that presented a correlation index (R2) of 0.964, at 5% probability, which characterizes the model with a best fit for the EC variable. It can be said, therefore, that the developed sensor is capable of being integrated into a monitoring system of the nutrient solution in a system.